Incidence and Determinants of Spontaneous Cardioversion of Early Onset Symptomatic Atrial Fibrillation - Marco Valerio Mariani; Nicola Pierucci; Agostino Piro; Sara Trivigno; Cristina Chimenti; Gioacchino Galardo; Fabio Miraldi; Carmine Dario Vizza (Medicina, 2022)
Atrial fibrillation (AF) is the most frequent chronic arrhythmia worldwide, and it is associated with significant morbidity and mortality, making it a considerable burden both to patients and the healthcare system. Nowadays, an early attempt to restore sinus rhythm in acute symptomatic AF through electrical or pharmacological cardioversion is the most common approach in the Emergency Department (ED). However, considering the high percentage of spontaneous cardioversion of paroxysmal AF reported by many studies, this approach may not be the ideal choice for all patients. In this manuscript we performed a review of the most relevant studies found in literature with the aim of identifying the main determinants of spontaneous cardioversion, focusing on those easy to detect in the ED. We have found that the most relevant predictors of spontaneous cardioversion are the absence of Heart Failure (HF), a small atrial size, recent-onset AF, rapid Atrial Fibrillatory Rate and the relationship between a previous AF episode and Heart Rate/Blood Pressure. A number of those are utilized, along with other easily determined parameters, in the recently developed “ReSinus” score which predicts the likelihood of AF spontaneous cardioversion. Such identification may help the physician decide whether immediate cardioversion is necessary, or whether to adopt a “watch-and-wait” strategy in the presence of spontaneous cardioversion determinants.